Thematic review series: the immune system and atherogenesis. Recent insights into the biology of macrophage scavenger receptors. - Greaves, D; Gordon, S (2005)
Scavenger receptors were originally defined by their ability to bind and internalize modified lipoproteins. Macrophages express at least six structurally different cell surface receptors for modified forms of LDL that contribute to foam cell formation in atherosclerosis. In addition to their role in the pathology of atherosclerosis, macrophage scavenger receptors, especially SR-A, play critical roles in innate immunity, apoptotic cell clearance, and tissue homeostasis. In this review, we highlight recent advances in understanding the biology of macrophage scavenger receptors as pattern recognition receptors for both infectious nonself (pathogens) and modified self (apoptotic cells and modified LDL). We critically evaluate the potential of scavenger receptors and their ligands as targets for therapeutic intervention in human disease.